(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To evaluate the effectiveness and safety of early cataract removal in cases of acute angle closure and primary angle closure. Methods: A prospective surgical intervention study without a control group implemented for 50 eyes of 40 patients with acute angle closure or primary angle closure with high intraocular pressure >21mmHg, anterior chamber angle still opened >1800, early cataracts were performed phacoemulsification with artificial intraocular lens implantation. Variables including intraocular pressure, visual acuity, amount of antihypertensive medication, anterior chamber angle opening status and intraoperative and postoperative complications were recorded and followed for 1 week, 4 weeks, 3 months, 6, and 12 months. Results: The visual acuity improved from 0.34 ± 0.18 to 0.06 ± 0.04 LogMAR (p<0.001), intraocular pressure from 37.20 ± 15.20 mmHg to 14.75 ± 2.10 mmHg (p<0.001), the number of glaucoma medication postoperative from 2.60 ± 0.49 to 0.18 ± 0.48. Cumulative completed success rates at 2 months, 4 months and 6 months are 96.0%, 94.0% and 89.9%, respectively, and remained unchanged until the end of 12 months of follow-up. Conclusions: Cataract removal surgery is effective and safe in the treatment of primary angle closure. It improves vision, lowers intraocular pressure, reduces the amount of antihypertensive medication, opens the angle and increases the depth of the anterior chamber angle.